SORDARIOMYCETES, KELOMPOK JAMUR YANG PALING BANYAK TERISOLASI DARI DAUN JARUM Pinus radiata DI AUSTRALIA - Istiana Prihatini (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2015)
Endophytes fungi have been extensively studied in conifer needles involving culture dependent methods, however little number have been conducted in Pinus radiata and no record have been reported from Tasmania. This study aimed to identify the major group of endophyte fungi isolated from P. radiata needles with varied conditions collected from Tasmania, Victoria and New South Wales plantation and confirmed by phylogenetic analysis of ITS gene. Sixteen endophyte fungi species as member of Sordariomycetes were isolated and Coniochaeta sp. 1 was the most frequently isolated species in this study.